UPAYA MENINGKATKAN KOMPETENSI GURU MELALUI LESSON STUDY DI SDI WOLOWONA 2 - Manggu Ngguna Raji; Fransiskus Korosando (Jurnal Cakrawala Ilmiah, 2022)
This research aims to improve teacher competency through lesson study activities. This type of research is a school action research with a qualitative descriptive approach. The research subjects consisted of 7 teachers. Data collected by observation, interview and documentation techniques. Data were analyzed by comparing the percentage of teacher competencies per cycle. The results showed that after applying the Lesson study there was an increase in teacher competence from the first cycle with an average percentage of 76% to 93% in the second cycle. Thus, it was concluded that lesson study can improve the competence of Wolowona 2 SDI teachers